2009
DOI: 10.1097/wnr.0b013e328326f82f
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide plasma levels are elevated in subcortical vascular dementia

Abstract: High levels of B-type natriuretic peptide (BNP), a serum marker of congestive heart failure, are associated with an increased risk for cognitive decline. However, no study has yet assessed this marker in different subtypes of dementia. We tested the hypothesis that BNP has a more significant association with vascular dementia than Alzheimer disease. Plasma BNP was measured in 15 patients with subcortical vascular dementia, in 19 Alzheimer patients without evidence of vascular comorbidity, and in age-matched co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
5
25
0
1
Order By: Relevance
“…12 In that study, BNP levels were predictive of cognitive function in 56 older adults with a history of cardiovascular disease. A second study found that BNP levels were associated with vascular dementia but not Alzheimer’s disease, 27 though more recently Buerger et al found that NP levels were associated with progression from mild cognitive impairment to clinical Alzheimer’s disease. 28 Our results are the first to show that NP levels are associated with poor cognitive function even among community-dwelling individuals unselected for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 97%
“…12 In that study, BNP levels were predictive of cognitive function in 56 older adults with a history of cardiovascular disease. A second study found that BNP levels were associated with vascular dementia but not Alzheimer’s disease, 27 though more recently Buerger et al found that NP levels were associated with progression from mild cognitive impairment to clinical Alzheimer’s disease. 28 Our results are the first to show that NP levels are associated with poor cognitive function even among community-dwelling individuals unselected for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 97%
“…Even though it is not known whether plasma BNP levels in the current study reflect brain or cardiac origin, CSF levels of BNP are significantly lower compared with plasma levels, suggesting that much or most plasma BNP is not brain derived. 51 Another marker identified in this study, SGOT (also known as aspartate transaminase), is typically associated with liver or skeletal muscle injury. SGOT levels were found to be lower in AD patients relative to control or MCI patients and showed significance (uncorrected for multiple comparisons) in the univariate and the multivariate analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, cardiac troponin T is a very sensitive and specific indicator of myocardial damage. A few studies report that serum levels of BNP [141, 142] or cardiac troponin T [143] are elevated in VCI-SSVD. These results need to be substantiated by other investigations to propose these molecules as relevant biomarkers for VCI-SSVD.…”
Section: Methodsmentioning
confidence: 99%